Wireless broadband access technologies - Ghanim, Mayada Faris (LAP LAMBERT Academic Publishing, 2013)
Wireless broadband technology has seen enormous growth in the last several years because of the demand for high quality multimedia services to mobile users. MC-CDMA is a combination of OFDM with CDMA; where synergistic effects can be obtained, such as enhancement of robustness against frequency selective fading and high scalability in possible data transmission rate. The main trend of this book is to improve MC-CDMA system by reducing PAPR. This book presents new broadband technology (MC-CDMA-FDMA) which depends on the current 4G uplink (SC-FDMA) system. The SC-FDMA system is elaborated with details and equations where the proposed MC-CDMA-FDMA system is shown to have advantages in terms of low bit error rate and low PAPR. Therefore MC-CDMA-FDMA technique can be one of the important topics for researchers who are looking forward for robust and high data rate wireless broadband technology.